2023
DOI: 10.1001/jamasurg.2023.2930
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Liraglutide, 3.0 mg, Once Daily vs Placebo in Patients With Poor Weight Loss Following Metabolic Surgery

Abstract: ImportanceMetabolic surgery leads to weight loss and improved health, but these outcomes are highly variable. Poor weight loss is associated with lower circulating levels of glucagon-like peptide-1 (GLP-1).ObjectiveTo assess the efficacy and safety of the GLP-1 receptor agonist, liraglutide, 3.0 mg, on percentage body weight reduction in patients with poor weight loss and suboptimal GLP-1 response after metabolic surgery.Design, Setting, and ParticipantsThe Evaluation of Liraglutide 3.0 mg in Patients With Poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…11,12 These findings align with prior studies which primarily reported mild to moderate GI side effects ranging in frequency from 30-50% with discontinuation rates of 5-9%. [13][14][15][16] GLP1RA AOMs do not appear to lead to a heightened risk of adverse events in patients who have previously undergone bariatric surgery.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…11,12 These findings align with prior studies which primarily reported mild to moderate GI side effects ranging in frequency from 30-50% with discontinuation rates of 5-9%. [13][14][15][16] GLP1RA AOMs do not appear to lead to a heightened risk of adverse events in patients who have previously undergone bariatric surgery.…”
Section: Discussionmentioning
confidence: 94%
“…18 Two randomized trials investigating Liraglutide in patients with prior bariatric surgery demonstrated efficacy with 8% additional weight loss (compared to placebo), and liraglutide was well tolerated in these trials with no SAE. 16,19 Two observational studies by Bonnett and Murvelashvili each reported that among patients with prior bariatric surgery, semaglutide can achieve 9 – 13% weight loss with a year of treatment. 20,21 In order to realize the potential of adjuvant AOM, rigorous studies are needed to develop practice guidelines that direct the use of AOMs as adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This section focuses on adolescents who are post-MBS and when they may benefit from the addition of AOM's as an adjunct therapy. The available MBS data for children [ [20] , [21] , [22] , [23] , [24] , 66 ] and adults [ [67] , [68] , [69] , [70] , [71] , [72] ] is examined for the variety of responses to MBS ( Table 2 ). This information is provided as guidance for the pediatric obesity medicine team.…”
Section: Introductionmentioning
confidence: 99%
“… −6 months of semaglutide treatment: −85 % of patients achieved >5 % weight loss −45 % reached >10 % weight loss −5% achieved >15 % weight loss. -No weight loss difference based on type of MBS Patients started semaglutide on average 64.7 months after MBS Mok et al., 2023 [ 69 ] 70 participants -poor weight loss response following RYGB or SG -randomized to receive 3.0-mg liraglutide (n = 35) or placebo (n = 35). -Poor response defined as < 20 % TBWL more than 1 year after MBS.…”
Section: Introductionmentioning
confidence: 99%
“…The BARI-OPTIMISE trial reported a difference of 8% further total body weight loss at 6 months between 35 patients randomized to receive liraglutide, 3.0 mg, and 35 patients randomized to placebo. 3 Similarly, the Gauging Responsiveness With a VerifyNow Assay-Impact on Thrombosis and Safety (GRAVITAS) trial using liraglutide, 1.8 mg, for persistent or recurrent diabetes in 80 patients with MBS demonstrated superior weight loss in the short-term compared with placebo as a secondary outcome. 4 The additional weight loss with associated favorable metabolic changes achieved with liraglutide…”
mentioning
confidence: 99%